2013
DOI: 10.4236/ib.2013.54016
|View full text |Cite
|
Sign up to set email alerts
|

Public Perception and Attitude towards Value Added Tax (VAT) in Nigeria

Abstract: This study assesses the level of tax education, particularly the level of understanding of VAT law amongst three categories of taxpayers in Nigeria. The data for the study were collected by means of structured questionnaires administered to the respondents. The analysis of results showed that most of the respondents have poor knowledge of VAT law in Nigeria, irrespective of their level of literacy, and that there was no significant difference in the amount of knowledge of VAT law amongst the three groups of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…In New Zealand, Maori and Pacific SMEs were found to have difficulties in tax payments as compared to Europeans and Asians (Yong, 2011). In Nigeria, different ethnic groups faced different social, technical and logistic problems when dealing with the VAT system (Oladipupo & Izedonmi, 2013).…”
Section: Figure 1: Conceptual Frameworkmentioning
confidence: 99%
“…In New Zealand, Maori and Pacific SMEs were found to have difficulties in tax payments as compared to Europeans and Asians (Yong, 2011). In Nigeria, different ethnic groups faced different social, technical and logistic problems when dealing with the VAT system (Oladipupo & Izedonmi, 2013).…”
Section: Figure 1: Conceptual Frameworkmentioning
confidence: 99%
“…However, the result on AVC shows a negative relationship with VAT compliance. Which can be linked to the findings from studies about the attitude towards VAT compliance depends on how the SME is treated by the government (Nyamwanza et al, 2014;Oladipupo & Izedonmi, 2013). In the same vein, the comments given by the respondents in the questionnaire also support the assertion that attitude towards compliance will be effective if other predictors are considered alongside attitude.…”
Section: Multiple Regression Analysismentioning
confidence: 66%
“…In relating attitude of SMEs to VAT compliance, some studies posit positive relationship between attitudes and tax (VAT inclusive) compliance (Benk et al, 2011;Nkwe, 2013), while other studies found that the AVC depends on how the SME or taxpayer is treated by the government. That is, the SMEs expect the government to provide its citizens with the basic needs, so as the value of the tax they are paying/remitting will be felt (Nyamwanza et al, 2014;Oladipupo & Izedonmi, 2013). The second construct that predicts intention in TPB is the subjective norms.…”
Section: Attitude Towards Vat Compliance (Avc)mentioning
confidence: 99%
“…alue Added Tax (VAT) is a multi-stage tax that is levied at various stages of production and distribution based on a percentage of the value added to goods produced or services provided (Oladipupo & Izedonmi, 2013;Omodero, 2022). Value added is equal to the sum of payments a firm makes to the factors of production used in the production of goods.…”
Section: Introductionmentioning
confidence: 99%